2015
DOI: 10.7326/m14-2693
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation for Clostridium difficile Infection

Abstract: U.S. Department of Veterans Affairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
242
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(251 citation statements)
references
References 50 publications
4
242
0
5
Order By: Relevance
“…Numerous authors joint on the imt, drekonia confirms positive results [10] and showed a pair of randomized controls. studying series of 28 and 5 cases, detected a recurrence in 2 patients, it concludes that imt may have a significant effect with a few short-term adverse effects for recurrent CDI.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Numerous authors joint on the imt, drekonia confirms positive results [10] and showed a pair of randomized controls. studying series of 28 and 5 cases, detected a recurrence in 2 patients, it concludes that imt may have a significant effect with a few short-term adverse effects for recurrent CDI.…”
Section: Discussionmentioning
confidence: 83%
“…since them, numerous cases have been described in the world literature, many doctors performed imt successfully, broody [3][4][5][6][7][8] observed that a second or in needed third transplantation is necessary to get good results, just as happened in our patient. Broody not only directed his attention to C. difficile, goes a little further and used imt in irritable bowel syndrome, myoclonusdystonia, ulcerative colitis and chronic fatigue syndrome [9].Numerous authors joint on the imt, drekonia confirms positive results [10] and showed a pair of randomized controls. studying series of 28 and 5 cases, detected a recurrence in 2 patients, it concludes that imt may have a significant effect with a few short-term adverse effects for recurrent CDI.…”
mentioning
confidence: 65%
“…As the disrupted gut microbiota is a key factor in the pathogenesis of C. difficile infection (CDI), FMT is increasingly used for recurrent or severe CDI. [105][106][107] In a recent systemic review involving 516 patients with recurrent CDI, 108 the overall success rate of FMT was reported as 85% for recurrent CDI and 55% for refractory cases. Although the evidence for such is limited, FMT for CDI seems safe.…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 99%
“…Still, the relative merits of selecting donors known or unknown to patients, though a subject of much speculation, are largely undefined. [22][23][24] Further research on the relative merits of donor selection and screening is needed.…”
Section: Current Donor Selection and Screening Guidancementioning
confidence: 99%